2011
DOI: 10.1074/jbc.m111.246637
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Recognition of a Human Chorionic Gonadotropin Epitope (hCGβ66–80) Depends on Local Structure Retained in the Free Peptide

Abstract: Human chorionic gonadotropin (hCG) is an important biomarker in pregnancy and oncology, where it is routinely detected and quantified by specific immunoassays. Intelligent epitope selection is essential to achieving the required assay performance. We present binding affinity measurements demonstrating that a typical ␤3-loop-specific monoclonal antibody (8G5) is highly selective in competitive immunoassays and distinguishes between hCG␤ 66 -80 and the closely related luteinizing hormone (LH) fragment LH␤ 86 -10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Subsequently, the remaining free surface amine groups on the PSNG electrode after Ab immobilization were blocked with 5% BSA in PBS for 10 min to avoid non-specific binding of hCG on the electrode. Then, the–NH 2 protected by tBOC was removed by immersing the electrode in 10 mM TFA solution prior to detection with the hCG target [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the remaining free surface amine groups on the PSNG electrode after Ab immobilization were blocked with 5% BSA in PBS for 10 min to avoid non-specific binding of hCG on the electrode. Then, the–NH 2 protected by tBOC was removed by immersing the electrode in 10 mM TFA solution prior to detection with the hCG target [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore likely that the presence of the b1-loop sequence, when long enough, will significantly strengthen binding of a single b3 loop to mAb 3468. For mAbs 4F9 and 8G5, previous binding experiments with linear b3-loop peptides in ELISA provided clear evidence for a b3-loop epitope, [37] but information other than that was not available. We observed that all three mAbs showed strong binding to tricyclic hCG mimic IVa by ELISA (Figure 3), virtually identical to that of hCG (less than twofold difference).…”
Section: Introductionmentioning
confidence: 99%